A mattress maker's daughter: the Renaissance romance of Don Giovanni de' Medici and Livia Vernazza - Dooley, Brendan Maurice (I Tatti studies in Italian Renaissance history, 2014)
Prologue -- The family business -- A mattress maker's daughter -- The heart of combat -- Writing the passions -- A place for things -- Mind over matter -- Durable goods -- Time and memory -- Postscript